Integrating Behavioral Economics into Decision-Making Models: A Bibliometric Review - Andi Afifah; Azaria Alifah Chiaradeuis; Elga Arjuna; Ardani Ardani; Disma Sang Wisangghabumi; Muhammad Aldi Gunawan; Muhammad Ramadhani Kesuma (Indo Publishing, 2026)
This study aims to analyze the development of literature on the integration of behavioral economics into decision-making models through bibliometric analysis, with emphasis on collaboration patterns, thematic evolution, and emerging research frontiers. Data were retrieved from the Scopus database using search queries encompassing behavioral economics, behavioral finance, prospect theory, bounded rationality, and cognitive bias combined with decision-making and financial management terms. A total of 394 articles were analyzed using VOSviewer software, covering co-authorship networks, co-occurrence of keywords, and text-data mapping. The analysis reveals well-established academic collaboration networks spanning multiple countries, with behavioral finance, investment decisions, and prospect theory emerging as central research themes. Co-occurrence mapping further identifies bounded rationality and cognitive bias as foundational constructs driving the integration of behavioral economics into financial decision-making models. These findings guide researchers and practitioners toward high-impact collaboration clusters and underexplored thematic gaps, supporting the design of more behaviorally informed financial decision-making frameworks. This study contributes a systematic bibliometric mapping of an expanding interdisciplinary field, providing the first comprehensive network view of how behavioral economics intersects with decision-making research across diverse geographic and institutional contexts.